A phase 1/2a dose-finding study and biomarker assessment of oral lisavanbulin in patients with high-grade glioma or glioblastoma - Lopez, Juanita Suzanne; Haefliger, Simon; Plummer, Ruth; Clement, Paul M.; Jeffry Evans, Thomas R.; Läubli, Heinz; Roth, Patrick; Kristeleit, Rebecca; Brazil, Lucy; Tabatabai, Ghazaleh; Wick, Antje; Wunderlich, Benjamin; et al. (Cell reports. Medicine, 2025)
Lisavanbulin is a prodrug of the microtubule-targeting agent avanbulin. Both avanbulin and lisavanbulin have demonstrated significant antitumor activity in several preclinical tumor models including glioblastoma. Previous human studies demonstrated that 48-h infusions of intravenous lisavanbulin were well tolerated with preliminary activity in recurrent glioblastoma. The current phase 1/2a study evaluates the safety and tolerability of once-daily oral lisavanbulin in patients with solid tumors or recurrent glioblastoma or high-grade glioma. Lisavanbulin is associated with profound, durable responses in a subset of patients with recurrent refractory grade 4 astrocytoma or glioblastoma. We present here the clinical and translational results from this trial, including a description of a response-predictive molecular signature that warrants further exploration in these tumor types of significant unmet need. The study is registered at ClinicalTrials.gov (NCT02490800).
Online verfügbar: 17. Juni 2025, Artikelversion: 17. Juni 2025
Gesehen am 19.01.2026